Making a Difference - Roger Sabbadini (PAGEPress Publications, 2024)
This is a personal account of one academic scientist who founded two biotechnology companies. Both companies were initially incubated within the walls of the university under a creative student incubator program whereby biology students could pursue their graduate academic degrees while gaining valuable biotechnology experiences. After the companies transitioned out of the university environment, the professor and his students pursued diagnostic and therapeutic drug development resulting in the completion of several clinical trials. The value of international scientific collaborations with colleagues at the University of Padova (Italy) is also described.